Hyperoodon (Hyperoodon) ampullatus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Hyperoodon (Hyperoodon) ampullatus (Forster 1770) [Balaena] ampullata Forster 1770, in: Kalm, Travels into N. Am., Vol. 1: 18. Type Locality: "See Mr. Pennant's [1769] British Zoology Vol. 3, p. 43, where it is called the beaked whale, and very well described;" Pennant (1769:43) gave Maldon (England) as the locality and 1717 as the date stranded. Vernacular Names: Northern Bottlenose Whale. Synonyms: Hyperoodon (Hyperoodon) butskopf (Bonnaterre 1789); Hyperoodon (Hyperoodon) latifrons Gray 1846; Hyperoodon (Hyperoodon) rostratus (Müller 1776). Distribution: North Atlantic: arctic to cold-temperate waters. The Mediterranean record represents a stray (J. G. Mead, 1989 b ). Conservation: CITES – Appendix I; IUCN – Lower Risk (cd). Discussion: Subgenus Hyperoodon . Reviewed by J. G. Mead (1989 b ). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 740, DOI: 10.5281/zenodo.7316519